Odpowiedź :
A) X+9=15
X=15-9
X=6
B) 2x+8=5+x
2x-x=5-8
X=-3
C) 6*x-2=8*x+12
6x-8x=12+2
-2x=14
X=-7
D) 2*x-8-5*x+6=5+4*x+7
-3x-2=12+4x
-3x-4x=12+2
-7x=14
X=-2
X=15-9
X=6
B) 2x+8=5+x
2x-x=5-8
X=-3
C) 6*x-2=8*x+12
6x-8x=12+2
-2x=14
X=-7
D) 2*x-8-5*x+6=5+4*x+7
-3x-2=12+4x
-3x-4x=12+2
-7x=14
X=-2
OdpowiedźOdpowiedź:
A)x+9=15
X=15-9
X=6|:1
X=6
B)2•x+8=5+x
2x+8=5+x
2x-x=5-8
X=-3|:1
X=-3
C)6•x-2=8•x+12
6x-2=8x+12
6x-8x=12+2
-2x=14|:(-2)
X=-7
D)2•x-8-5•x+6=5+4•x+7
2x-8-5x+6=5+4x+7
2x-5x-4x=7+5-6+8
-7x=14|:(-7)
X=-2
Mam nadzieję, że pomoglem. Licze na naj :)